Um estudo sobre o comportamento de investidores e os fatores intervenientes na tomada de decisão em ambiente virtual de uma organização financeira - Eliana Marcia Martins Fittipaldi Torga (2017)
The objective of this research is to investigate the factors involved in investor decision-making, based on qualitative and quantitative approaches in a financial and virtual organization environment. This inquiry-based research was fully answered and it showed that decision-making is the result obtained by combining various factors in an individual and collective construction traversed by historicity, culture, values, emotions, senses, power relations, and social contexts. Thus, decisions are the result of an individual and collective agency, in a fraction of a moment and a context, adaptable to the changes that may or may not point to personal and social well-being. This thesis is configured as a political action, in that it presents, from a multidimensional perspective, the phenomena observed in the field of Finance. The theoretical itineraries that are part of the intra-discourse are the rationality and the mechanisms for decision-making, whatever may be the cognitive, emotional, and social aspects of it. This study confronts the ideology of economic thinking, for which human issues studies should be focused only on the paradigm of rationality and predictability of human affairs, but it recognizes the importance of rationalizing technical and organizational measures for decision-making. A research was conducted on the targeted study, from the immersion of the researcher in the research environment, in a netnography, declaring herself as a participant in the research. Semi-structured interviews were conducted with investors to deepen the subjects studied and to attain a qualitative analysis based on content analysis and a quantitative and statistical analysis involving the discursive segments posted by the participants in the Forum chosen for immersion and analysis. In order to elucidate the topics listed, theories of finance from traditional to modern to behavioral, the social, cognitive, and behavioral approaches of Psychology, Sociology of Knowledge, and Sociology in Finance were considered for better understanding of the social construction aspects of the field of Finance, with the support of speech production and the analysis of senses. It started from the problem identified in the area of Finance: the decision-making behavior of agents in the financial market, which go against appropriate behavior for a globalized and sustainable market and are producing global financial crises. The study focused on an ordinary problem, aiming to examine the elements capable of explaining them, as well as providing elements to subsidize solutions. The epistemological position was Interpretivism. The sociological vision that underlies the research was the social construction of reality. The perspective of the study is inter and transdisciplinary, based on theories of Finance, Psychology, and Sociology. The sub-themes covered considered individual aspects, such as cognitive, emotional and behavioral, and social, such as organizational structure, modes of organization and interaction, power relations, communication, and language. The results of the quantitative survey confirmed the findings of the qualitative approach. The theoretical frameworks chosen for the analysis of decision factors were positively correlated as criteria that build decision-making, which are: cognitive behavioral aspects, psychosocial characteristics, emotions, social influence, power relations, and hierarchy. The social groups studied are differentiated based on the modes of organization, rules, and interaction, defined by a hierarchical organization. Social groups are adaptable in their structure and modes, depending on the personalization of those leading to social organization, indicating the mutual influence among the participants in role-based interaction and in positions of hierarchy and power. Investors are intrinsically subjective, not rational. Finance, being a social science, needs to incorporate and assume its "social" role in a practical way, not just theoretical. This change will lead to an understanding of financial market behavior, with a view to building a system based on the society that one wishes to have. The human being is much more than the selfish and opportunistic being. He is also a multidimensional and ethical being, biologically complex, physiologically dynamic, psychically oriented and built, socially supported, formed by history and by the environment, permeated with emotions, and he is adaptable / pliable. This research contributed to the field of Finance, discussing the matters of this area, for a rereading, creating opportunities for the realignment of this discipline, which is so important for human sustainability; to the practice of applied research, through field netnography, which became a living laboratory for a real experience of the activity in the studied field; to the use of qualitative and quantitative techniques, which together allowed a better understanding of the object-oriented analysis; to the identification of the factors that intervene in decision-making; to the expansion of research topics in Behavioral Finance, whose work has prevailed in the functionalist and quantitative paradigms for the study of the behavior of financial agents; to the elaboration of other studies and the deepening of this researchs findings; to reflections on the need for new approaches involving the formation and training of professionals who will work in the area of Finance and correlates of it, preparing them to deal with the influence of social, cognitive, and emotional aspects, enabling a more adequate preparation for their performance in the financial market; to reflections on different ways to perceive investment and risk opportunities, which may be further explored in other studies on segmentation of clients according to their preferences in the Investment Market; to the knowledge and reinforcement of the ethical and objective values of the discipline, financial well-being, which along with other dimensions, can lead to social welfare; to the field of interdisciplinary researches; to the underlining of the importance of a transdisciplinary work for the elucidation of problems that are not circumscribed to the analysis of a single field of knowledge; and to the understanding of this dialogical human being, who is the constructor of the reality that surrounds him. This work offers the possibility of constructing future researches, such as the behavior of the investors, segmented by individuals, in terms of the dimensions of culture, gender, education and qualification, life cycle, and experience; studies on the stress of this professional activity and ways of preventing this risk; the deepening of the theoretical constructs analyzed and their influence on decisions; identification and analysis of regulations for the sustainable functioning of the market; and the formulation of new teaching technologies for the training of new financial analysts, so that they can be aware of the cognitive traps, the potential of their emotions, and the construction of the rules of the bargaining game present in the social context.